Development of cognitive processing and judgments of knowledge in medical students: Analysis of progress test results. (1st November 2016) - Cecilio-Fernandes, Dario; Kerdijk, Wouter; Jaarsma, A. D. (Debbie) C.; Tio, René A.
Abstract: Background: Beside acquiring knowledge, medical students should also develop the ability to apply and reflect on it, requiring higher-order cognitive processing. Ideally, students should have reached higher-order cognitive processing when they enter the clinical program. Whether this is the case, is unknown. We investigated students' cognitive processing, and awareness of their knowledge during medical school. Methods: Data were gathered from 347 first-year preclinical and 196 first-year clinical students concerning the 2008 and 2011 Dutch progress tests. Questions were classified based upon Bloom's taxonomy: "simple questions" requiring lower and "vignette questions" requiring higher-order cognitive processing. Subsequently, we compared students' performance and awareness of their knowledge in 2008 to that in 2011 for each question type. Results: Students' performance on each type of question increased as students progressed. Preclinical and first-year clinical students performed better on simple questions than on vignette questions. Third-year clinical students performed better on vignette questions than on simple questions. The accuracy of students' judgment of knowledge decreased over time. Conclusions: The progress test is a useful tool to assess students' cognitive processing and awareness of their knowledge. At the end of medical school, students achieved higher-order cognitive processing but their awareness of their knowledge had decreased.